39.9k views
4 votes
Use the method of completing the square to transform the quadratic equation into the equation form (x+p)^2 = q

-4+4x+x^2

User Niederee
by
5.5k points

2 Answers

1 vote
the answer is -71/36
User Urszula
by
4.9k points
5 votes

Answer:

To transform the quadratic equation into the equation form (x + p)2 = q we shall proceed as follows:

3+x-3x^2=9

putting like terms together we have:

-3x^2+x=6

dividing through by -3 we get:

x^2-x/3=-2

but

c=(b/2a)^2

c=(-1/6)^2=1/36

thus the expression will be:

x^2-x/3+1/36=-2+1/36

1/36(6x-1)²=-71/36

the answer is:

1/36(6x-1)²=-71/36

Explanation:

User Geoffreys
by
5.1k points